PEMBUATAN MULTIMEDIA FISIKA ONLINE UNTUK PEMBELAJARAN ILMU PENGETAHUAN ALAM SMP KELAS VIII - Rahmi Seftina (Universitas Negeri Padang, 2014)
The alternative multimedia can support the learning process in the classroom. It can be used to reach the learning outcome, solution to support the learning process is physics online multimedia. The purpose of this research are to produce good description, a valid, a practical, and a effective online multimedia. The type of research was Research and Development (R&D). The experiment subject of this research was 24 students in grade VIII of Junior High School 1 Padang. The instruments that used to collect of data were the validation sheet, practicability sheet, and sheet of multiple choice test. Base on the data analysis that has been done, it could be presented four research results. First, design Physics online multimedia consist of subject matter, exercise and task, test, game, and quiz. Second, Physics online multimedia has high validity score 87.94. Three, the value of practicality Physics online multimedia according to teacher and students each other 88,50 and 78,15. Finally, physics online multimedia was effective in implementing Physics learning on grade VIII of Junior High School 1 Padang that indicated by increasing of significant learning outcome both cognitive domain and affective domain